(untitled) (CIPEEX, 2025)
Inclusive education represents the essence of an accessible, egalitarian, diverse and democratic school, based on justice, equity and the social right of man, whose compulsory observance in a State of Social Law understands that these rights are primarily aimed at improving the living conditions of the underprivileged, thus incorporating the contemporary principles that defend human rights. In this context, this study aims to analyze the (in)effectiveness of public policies for educational inclusion in the municipality of Senador Canedo. In order to achieve the desired results, the following specific objectives were formulated: i) to address the historical and social perspectives of inclusive education in a global context; ii) to discuss the right to education in the Brazilian legal system; and, iii) to analyze the (in) effectiveness of public policies for educational inclusion in the municipality of Senador Canedo. To carry out the research, the qualitative method was used, with analysis of legal documents and journalistic articles, as well as the bibliographical review method to compose the theoretical framework. In this sense, research into the effectiveness of public education policies in Senador Canedo is important because it can reveal systemic and cultural barriers that prevent the full realization of educational inclusion, as well as highlighting good practices that can be replicated in other locations. Therefore, by addressing the issue of inclusive education and the effectiveness of public policies in Senador Canedo, we hope to contribute to the improvement of educational strategies, promoting a more accessible and welcoming school for all.